Failure of Eruption of Permanent Tooth - Bhuvaneswarri, J (Int J Appl Basic Med Res, 2018)
Primary failure of eruption (PFE) is a rare condition that can lead to posterior open bites. It is difficult to diagnose and difficult to treat. PFE appears to be a condition that predominantly affects the molar dentition. The increased frequency of hypodontia in affected individuals and common findings of a family history regarding tooth eruption problems suggests a significant genetic component to the etiology of this rare condition.